2022
DOI: 10.1101/2022.08.30.22279381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development and validation of a dynamic prediction model for unplanned ICU admission and mortality in hospitalized patients

Abstract: Frequent assessment of the severity of illness for hospitalized patients is essential in clinical settings to prevent outcomes such as in-hospital mortality and unplanned ICU admission. Classical severity scores have been developed typically using relatively few patient features, especially for intensive care. Recently, deep learning-based models demonstrated better individualized risk assessments compared to classic risk scores such as SOFA and NEWS, thanks to the use of aggregated and more heterogeneous data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…38 Our study results suggested that the heart rhythm shockability trajectory during CPR may also be a prognostic factor. Previous studies have shown that dynamic prediction models, 39,40 which can continuously update as more information becomes available, may offer the advantage of delivering swift and precise risk predictions in response to new data. Future studies may further investigate whether intra-arrest collected information 41,42 or heart rhythm shockability may improve the performance of prediction models for OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…38 Our study results suggested that the heart rhythm shockability trajectory during CPR may also be a prognostic factor. Previous studies have shown that dynamic prediction models, 39,40 which can continuously update as more information becomes available, may offer the advantage of delivering swift and precise risk predictions in response to new data. Future studies may further investigate whether intra-arrest collected information 41,42 or heart rhythm shockability may improve the performance of prediction models for OHCA.…”
Section: Discussionmentioning
confidence: 99%